(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Evaluation of the quality of preschool education is currently an important aspect of the system of preschool education in many countries. The emergence of the concept of "quality of education" was due to a change in attitudes towards preschool education throughout the 20th century. Here we would like to note a number of circumstances that led to the raising of the question of the need to develop a system for assessing the quality of preschool education